2013
DOI: 10.7196/sajhivmed.980
|View full text |Cite
|
Sign up to set email alerts
|

High rate of virological re-suppression among patients failing second-line antiretroviral therapy following enhanced adherence support: A model of care in Khayelitsha, South Africa

Abstract: Objective. To describe and evaluate the outcomes of a support programme for patients with virological failure while receiving second-line antiretroviral therapy (ART) in South Africa. Method. We described a comprehensive medical and counselling patient support programme for patients receiving secondline ART and with two consecutive viral loads (VLs) >1 000 copies/ml. Patients with >3 months follow-up and at least one VL measurement after inclusion in the programme were eligible for analysis. Results. Of 69 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 19 publications
5
25
2
Order By: Relevance
“…However, our results do show that a large proportion of patients with unsuppressed viral loads on second‐line can be maintained on these regimens. This is similar to the findings of a study conducted in the Western Cape where 68% (95% CI 54–82%) of patients failing second‐line ART achieved virologic resuppression with intensified adherence counselling . This is important because third‐line regimens are expensive and not available in most resource‐limited settings.…”
Section: Discussionsupporting
confidence: 84%
“…However, our results do show that a large proportion of patients with unsuppressed viral loads on second‐line can be maintained on these regimens. This is similar to the findings of a study conducted in the Western Cape where 68% (95% CI 54–82%) of patients failing second‐line ART achieved virologic resuppression with intensified adherence counselling . This is important because third‐line regimens are expensive and not available in most resource‐limited settings.…”
Section: Discussionsupporting
confidence: 84%
“…This approach might allow early tailored adherence interventions before virologic failure and selection of resistance mutations to facilitate viral re-suppression and optimise treatment outcome [25]. At less than US$50 per sample, one could imagine for instance the development and use of a simple point of care test that reported 'absence' or 'presence' of the drug at any pre-determined level.…”
Section: Discussionmentioning
confidence: 99%
“…A threshold of 80% adherence measured by pharmacy refill in the previous 4 months could be used to identify patients needing enhanced adherence support and rationalise use of VL testing in resource-limited settings. Most patients on second line ART experiencing VF were able to achieve virologic suppression with intensified adherence support in a study at a clinic in South Africa [ 21 ]. VF on second line ART is likely a result of poor adherence rather than resistance as several studies have found a low proportion of major PI mutations in patients with VF on second line ART [ 10 ]-[ 12 ].…”
Section: Discussionmentioning
confidence: 99%